Contemporary business report writing - Kuiper, Shirley (Australia ; Mason, OH : South-Western Cengage Learning, 2009)
The text contains general guides for report writing; specific guides for a variety of common business reports; illustrations and examples of the guides presented; and an abundance of application exercises.
Includes bibliographical references and index.
nif 23/04/13, ijb 10/04/2019
Loans
Keywords: Business report writing; Report writing